Profissionalização da estrutura administrativa de empresas familiares: comércio varejista de materiais de construção - Ribeiro, Gilberto Cesar [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
One of the existing business models is the family business. This paper deals with the structure of family businesses. With the purpose to analyzing the input and output processes of goods, and management behavior in decision-making, looking for the professionalization of the family business administration. This paper is a case study in a construction materials shop, with an applied research due to their nature, according to his purpose takes the characteristic of exploratory research, using interviews, observation and analysis of company data. During the analysis of processes in the company were noted some shortcomings. Given this fact, made the comparison with the theories found, proposals were generated improvements to be accomplished within the company structure
Keywords: Empresas familiares; Cultura organizacional; Comercio varejista; Lean manufacturing